Long-term results of combined treatment of patients with early breast cancer after conserving therapy - Kędzierawski, Piotr; Ciepiela, Izabela; Florek, Agnieszka; Bocian, Artur; Macek, Paweł; Howorus, Marlena; Góźdź, Stanisław (Medical Studies/Studia Medyczne, 2016)
Introduction: Mastectomy was the most frequently used method of surgical treatment of patients with breast cancer in the Kielce Region. With the opening of the Surgical Oncology Clinic and the Department of Radiotherapy in the Holycross Cancer Centre, a larger number of patients could undergo breast-conserving therapy. Aim of the research: The objective of the study was evaluation of the remote outcome of treatment of patients with breast cancer after conserving therapy. Material and methods: During the period 2001–2005, in the Holycross Cancer Centre, 65 women with early-stage breast cancer underwent breast-conserving therapy. The patients were subjected to combined treatment. The total period of observation was from 105 to 143 months; median 113 months. In statistical analysis the distribution of the investigated variables was examined using the Kolmogorov-Smirnov test and Lillefors test. The significance of the differences between the variables analysed was tested by means of the Mann-Whitney U test. The probability of survival without symptoms of the disease was estimated by the Kaplan-Meier method. The cosmetic outcome was evaluated based on individual medical observations and a questionnaire developed at the Department of Radiotherapy. Results and conclusions : Relapse of the disease was noted in 5 (8%) patients. Local recurrence occurred in 2 (3%) patients. In the analysed group, the 2-, 3-, 5-, and 10-year survival rates without symptoms were 98.5%, 96.9%, 95.4%, and 95.4%, respectively. No statistically significant differences were found between the groups of patients with and without cancer. In the majority of patients, after many-year observation, the cosmetic outcome is good.